2017
DOI: 10.1016/j.bbi.2017.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral inflammatory cytokines and immune balance in Generalised Anxiety Disorder: Case-controlled study

Abstract: Introduction-Previous investigations have demonstrated that major depression is associated with particular patterns of cytokine signalling. The primary aim of this study was to examine peripheral pro-inflammatory and anti-inflammatory cytokines and immune balance in generalised anxiety disorder (GAD).Methods-A case-controlled cross-sectional study design was employed: 54 patients with GAD and 64 healthy controls were recruited. Participants completed self-report measures of anxiety and depression. Two pro-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
109
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(118 citation statements)
references
References 73 publications
6
109
0
3
Order By: Relevance
“…Although depression has been studied more widely in relation to inflammation (Dowlati et al, 2010;Schiepers, Wichers, & Maes, 2005), it is important to understand if the anticipatory-based state of anxiety may produce dysregulated inflammatory responses (or vice versa) and put an individual at an increased risk of experiencing long-term negative health consequences. Further, these findings support several other studies that highlight the potential for trait anxiety to be associated with a dysregulated immune response (Hou et al, 2017;O'Donovan et al, 2010). The findings of the current meta-analysis are somewhat contrasting to a previous meta-analysis of OCD and inflammation, which identified depression moderating the relationship between OCD and TNF- (Gray & Bloch, 2012).…”
Section: Discussionsupporting
confidence: 72%
“…Although depression has been studied more widely in relation to inflammation (Dowlati et al, 2010;Schiepers, Wichers, & Maes, 2005), it is important to understand if the anticipatory-based state of anxiety may produce dysregulated inflammatory responses (or vice versa) and put an individual at an increased risk of experiencing long-term negative health consequences. Further, these findings support several other studies that highlight the potential for trait anxiety to be associated with a dysregulated immune response (Hou et al, 2017;O'Donovan et al, 2010). The findings of the current meta-analysis are somewhat contrasting to a previous meta-analysis of OCD and inflammation, which identified depression moderating the relationship between OCD and TNF- (Gray & Bloch, 2012).…”
Section: Discussionsupporting
confidence: 72%
“…A number of biologic mechanisms may explain this increased risk and evidence suggests that the inflammatory nature of AS could be closely tied to depression and anxiety. As observed in patients with AS [27], individuals with depression and anxiety have also been shown to have elevated levels of proinflammatory cytokines, including tumour necrosis factor alpha and interleukin-6 [28,29].…”
Section: Discussionmentioning
confidence: 83%
“…In their 2016 study on the prevalence of depression and anxiety among patients with rheumatic diseases (n = 514) including 44 with AS, Anyfanti et al also assessed treatment of psychiatric complications and reported considerable under-treatment with less than 10% of AS patients receiving an antidepressant or antianxiolytic [32]. Finally, given the potential role of inflammation in the relationship between AS and depression [27][28][29], treatments for AS, particularly antitumour necrosis factor (anti-TNF) agents, may also impact depression as suggested in prior clinical study [33].…”
Section: Discussionmentioning
confidence: 99%
“…A number of biologic mechanisms may explain this increased risk and evidence suggests that the inflammatory nature of AS could be closely tied to depression and anxiety. As observed in patients with AS (27), individuals with depression and anxiety have also been shown to have elevated levels of proinflammatory cytokines, including tumour necrosis factor alpha and interleukin-6 (28,29).…”
Section: Discussionmentioning
confidence: 76%